2003
DOI: 10.1136/jcp.56.6.433
|View full text |Cite
|
Sign up to set email alerts
|

Digital slide and virtual microscopy based routine and telepathology evaluation of routine gastrointestinal biopsy specimens

Abstract: Aims: To evaluate a recently developed digital slide and virtual microscope system, and to compare this method with optical microscopy on routine gastrointestinal biopsy specimens in both local and remote access modes. Methods: A fully computer controlled commercial microscope was used. The scanning program included object detection, autofocus, and image compression algorithms. The overall hard disk space for a gastric biopsy was between 30 and 50 MB and the scanning time was between 20 and 40 minutes. Haemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 24 publications
2
86
0
5
Order By: Relevance
“…Similar diagnostic results were obtained with both VMR and OMR, including similar severity and incidence rates . Other studies reported in the literature have also shown high diagnostic corresponding rates for virtual microscopy and conventional microscopy readings (Steinberg and Ali, 2001;Molnar et al, 2003;Gagnon et al, 2004;Lundin et al, 2004).…”
Section: Comparison Of the Vmr And Omrmentioning
confidence: 80%
See 3 more Smart Citations
“…Similar diagnostic results were obtained with both VMR and OMR, including similar severity and incidence rates . Other studies reported in the literature have also shown high diagnostic corresponding rates for virtual microscopy and conventional microscopy readings (Steinberg and Ali, 2001;Molnar et al, 2003;Gagnon et al, 2004;Lundin et al, 2004).…”
Section: Comparison Of the Vmr And Omrmentioning
confidence: 80%
“…With appropriate spatial and color/intensity resolutions, a digital slide could virtually represent the original glass tissue slide. Therefore, diagnosis based on the virtual slide could be acceptable (Costello et al, 2003;Molnar et al, 2003;Kumar et al, 2004;Helin et al, 2006).…”
Section: Requirement For Toxicologic Pathology and Automatedmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of these are completed and others are under construction (see http://www.path.uiowa.edu/ virtualslidebox/). More recently, application to service pathology has begun at a number of institutions (Molnar et al, 2003;Gagnon et al, 2004;Helin et al, 2006;Dee et al, in press).…”
Section: Introductionmentioning
confidence: 99%